Speckle Noise Reduction Method Based on Fuzzy Approach for Synthetic Aperture Radar Images - Santoso, Ardhi W.; Bayuaji, Luhur; Jasni, Mohamad Zain; Pebrianti, Dwi; Lim, Tien Sze; Habibah, Lateh (Universiti Malaysia Pahang, 2016)
Synthetic Aperture Radars (SAR) are classified as active sensors. It has been capable of producing images with high spatial resolution, and able to observe at day and night and in all-weather condition. With these advantages, SAR image becomes more popular than the Optical image. SAR image formation process led to speckle noise; it causes difficulties in the process of interpretation and analysis of SAR images. Fuzzy approach is a technique that can be used to reduce speckle noise. It has been used in the ultrasonic image in the medical field and showed good performance in image filtering to reduce speckle noise. Implemented to SAR images for reduce speckle noise by replacing the center pixel local neighbor Frost's with digital numbers that calculate by fuzzy filter. Proposed filters applied into a homogeneous and heterogeneous area in SAR images, aims to measure the robustness of the proposed filters in speckle noise reduction and texture preservation, mainly in homogeneous areas. All of areas is filtered using proposed filters; that's, Frost-TMED, Frost-ATMED, Frost-ATMAV and Frost-TMAV combination. Evaluation has been made, to measure the performance of filters, major in speckle noise reduction and texture preservation. The experiment result shows that the combination of Frost-TMAV has the highest performance. It has been verified that the Frost-TMAV filtering approach is performing better than the other filters, which mean being able to produce good-quality images than other filters. It also produces an obvious example of speckle reduction processing; features of tissues are enhanced and a good preserve on texture. The result shows that fuzzy approach has robustness to reduce speckle noise in SAR image, especially in ALOS-PALSAR’s raw data, which require clarity of the image for further processing.